Optimization of internal medicine learning with a case-study - Syvolap, V. D.; Soloviuk, О. О.; Nasarenko, О. V.; Soloviuk, О. A.; Сиволап, Віктор Денисович; Назаренко, Олена Валеріївна; Солов'юк, Олександр Олегович (Warsaw: RS Global Sp. z O.O., 2017)
The purpose of this work was an analysis of information about the possibility of using the case study method in teaching discipline "Internal Medicine" for medical students. The main purpose of the case method is to conduct an analysis of a particular situation by working with a group of students. Different approaches can be used depending on the topic. Illustrative study situations, applied exercises, situations with or without problem generation, presentation of any digital data, etc. can be presented as case studies. This teaching method is very effective in the study of medical disciplines. Application of the case method in the educational process can improve the quality of studying the teaching material, promote dialogue between the teacher and the student on an equal level, increase the interest of students in the study of the discipline "Internal Medicine".
Keywords: Education; Case-study; Internal Medicine; clinical situation